(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
The stratigraphy of clayey and sandy beds outcropping in Val di Pugna locality near Siena (Tuscany, Italy) celebrated for the past finds of fossil mammalian remains, is studied here. The research is aimed to date and define the depositional environment of the sediments that yielded fossil bones of known provenance. Two sequences have been studied in detail; they are located near the hamlets of Ruffolo and Case il Poggio, where both marine and land mammal remains had been found. The integrated biostratigraphic analysis of the planktonic foraminifers and calcareous nannoplankton indicates that the deposits straddle the transition from the Zone MPL3 to MPL4 of the planktonic foraminifer biostratigraphic scale, which is correlated with the Reticulofenestra pseudoumbilicus Zone (MNN14-15 Zone) of the calcareous nannoplankton scale. The sedimentary characters and the faunal content are suggestive of a progressively deepening marine environment, with a transition from upper shoreface deposits to lower shoreface-offshore deposits. The vertebrates include a cetacean (Tusciziphis crispus) and a sirenid (Metaxyterium gervaisi) amongst the marine mammals, while the land mammals are represented by a rhino (Stephanorhinus jeanvireti) and a bovid (Alephis lyrix). The sirenid remains are likely the only autochthonous elements because of their ecologic consistency with the depositional environment of the embedding sediments. The other fossil specimens are interpreted here as parts of decaying and floating carcasses that deposited their bones as they drifted away, inflated by decomposition gasses. The biostratigraphy of the sites permits to date the fossil bones. Noteworthy occurrences are those of Stephanorhinus jeanvireti and Alephis lyrix in levels correlated with Zone MN14, since they are usually reported in Zone MN16 and Zone MN15 assemblages, respectively.